Signature Analysis of the Hydraulic Accumulators when Using in Energy Recovery Systems in Automobiles - Korobko, Bogdan; Vasyliev, Oleksiy; Rohozin, Ivan; Vasyliev, Ievgen (International Journal of Engineering and Technology, 2018)
The design of a car, which includes the hydrostatic transmission with a kinetic energy recovery system oriented at large-load freights under the conditions of frequent acceleration and repeated brakings has been proposed in this article. Rationale for choosing hydro accumulators for a dream-car (prototype vehicle) has been fulfilled, as well as energy storage battery capacity and the influence of these batteries on the car performance in different operating modes has been carefully analyzed.Â Â